PEMANFAATAN COST PROFIT VOLUME ANALISYS - Elfreda Aplonia Lau (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2020)
This descriptive research aims to describe cost profit, volume analysis and show its use in determining the minimum production quantities that must be produced and sold in various conditions where changes in selling prices, changes in variable costs, changes in fixed costs or changes in the composition of the sales mix. Do these changes have an impact on cost profit volume analysis or BEP?This study also aims to apply the use of Cost profit volume analysis in sales or production planning, planning for normal selling prices, planning for production methods and determining the plant's closing point (shut down point)The results showed that: 1. BEP can change because of a. there is a change in the selling price while the costs are fixed, there will be a change in the Break Even Point , if there is an increase in the selling price it will decrease the BEP point. And vice versa if there is a determination of the selling price it will raise the BEP point. b) changes in variable costs with fixed selling price conditions, there will be a change in Braek Even Point points in proportion to these changes, i.e. if an increase in variable costs will increase the BEP point. And vice versa if there is a variable cost determination will reduce the point BEP.c) changes in fixed costs with the variable costs and fixed prices, there will be a change in the Braek Even Point point proportionally to these changes, if an increase in fixed costs will increase the point BEP And vice versa if there is a fixed cost determination will reduce the BEP point. 2. BEP can be used for sales or production planning in order to obtain the desired profit. 3. BEP can be used for planning the normal selling price, ie the selling price of a product that can help the company achieve the desired profit target.4 BEP can be used in the selection of production methods (labor intensive or capital intensive) .5 BEP can be used to close the company or not.